SISTEM MONITORING DAN CONTROLLING MOTOR HOIST CRANE BERBASIS IOT - Muhammad Bayu Aji Tetuko (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2025)
Companies engaged in the steel industry utilize machines and lifting equipment to support productivity. Hoist cranes are lifting machines widely used in companies, ports, factories, warehouses, and the steel industry. They are mechanical devices used to move objects from one place to another. However, one common problem with hoist cranes is the occurrence of overcurrent in the motor, which triggers the circuit breaker to trip. In such cases, the operator must climb onto the chassis or body of the hoist crane to reset the system manually. To address this issue, an IoT-based hoist crane monitoring and control system was developed using a power sensor module to measure real power (Watts), voltage (Volts), current (Amperes), and power factor (pf) in real time via an internet connection. The collected data is then processed by a microcontroller. The main components used in this system include the ESP32 microcontroller, PZEM-004T current sensor, and relay. The results of this study demonstrate that the IoT-based hoist crane motor monitoring and control system functions properly and meets the research objectives. Keywords: Hoist Crane, ESP32 Microcontroller, PZEM-004T Sensor, IoT.